Effect of Upper Lid Blepharoplasty Surgery on Corneal Topography and Corneal High-Order Aberrations - Ulas, Mehmet Goksel; Tukenmez Dikmen, Nejla (Facial Plastic Surgery, 2023)
The objective of this study was to prospectively investigate the effect of upper eyelid blepharoplasty surgery for dermatochalasis on corneal topographic data and high-order aberrations (HOAs). Fifty eyelids of 50 patients with dermatochalasis who underwent upper lid blepharoplasty surgery were prospectively studied. A Pentacam (Scheimpflug camera, Oculus) device was used to measure corneal topographic values, astigmatism degree, and HOAs before and at 2 months after upper eyelid blepharoplasty. The mean age of the patients included in the study was 55.96 ± 12.4 years, 40 (80%) were female and 10 (20%) were male. We found no statistically significant difference in the pre-and postoperative values of corneal topographic parameters (p > 0.05 for all). In addition, we observed no significant postoperative change in the root mean square values of low, high, and total aberration values. In HOAs, we detected no significant change in spherical aberration, horizontal and vertical coma, and vertical trefoil; we only found a statistically significant increase in horizontal trefoil values after surgery (p < 0.05). In our study, we found that upper eyelid blepharoplasty did not cause significant changes in corneal topography, astigmatism, and ocular HOAs. However, studies are reporting different results in the literature. For this reason, it is important for patients considering upper eyelid surgery to be warned about visual changes that may occur after surgery.
Keywords: upper lid blepharoplasty; dermatochalasis; corneal topography; corneal high-order aberrations